BRIDGING CULTURES A COMPARATIVE STUDY OF UZBEK AND RUSSIAN WEDDING TRADITIONS - Turdialiyeva Elnura (KONFERENSIYALAR, 2025)
Annotation. This article explores the wedding traditions, rituals, and matchmaking customs in Russian and Uzbek families. Uzbek wedding traditions, which have evolved over centuries, are renowned for being among the oldest in the world. In Uzbekistan, a wedding is far more than a festive occasion; it encompasses a series of traditional ceremonies conducted in a specific sequence. This intricate process can span from a month to an entire year, reflecting the importance of selecting a suitable bride for young Uzbeks. Families meticulously investigate the prospective bride, her background, and her environment to ensure she is a worthy life partner. The initial ceremony, known as “Hatim”, takes place at the bride’s residence, where close family and friends gather to bless the couple and exchange gifts. Following this is the "Nikah," the official wedding ceremony, which is held either in a mosque or at the groom’s home. After the “Nikah”, a grand feast is hosted, bringing together relatives and friends to celebrate the union. The festivities continue the next day with the “Kelin Salom” ceremony, marking the bride’s first visit to her husband’s home.